THE EFFECT OF EDUCATION BACKGROUND AND HALAL SOCIALIZATION ON THE INTEREST OF SMALL MICRO ENTERPRISES (UMK) IN CERTIFYING HALAL PRODUCTS (International Conference on Social and Islamic Studies, 2022)
Halal certification is an issue that is currently developing in the business world in Indonesia, especially businesses based in the food sector. This is due to the Mandate of Law No. 33 of 2014 which requires all products circulating in Indonesia to be halal certified. In reality, there are not a few business actors, especially micro and small businesses, who have not certified halal products. Therefore, it is interesting to study whether the background of education and socialization about halal affects their interest in certifying halal products or not. This study used a quantitative research design with 100 respondents consisting of MSEs in Bangkalan Regency. The data of this study was taken with a questionnaire instrument and analyzed with the help of the Smart PLS statistical application. This study concluded that the background of MSE Education and socialization about halal certification has a positive and significant effect on the interest of small micro businesses in certifying halal their products. The results of this research will be very useful for related agencies to increase MSE awareness of the importance of halal certificates for their products.